A Concise and Versatile Total Synthesis of All Stereoisomers of Tarchonanthuslactone - Huang, Shuangping; Liu, Dongwang; Tang, Linjun; Huang, Feifei; Yang, Wei; Wang, Xiaoji (Synlett, 2015)
We describe the versatile and concise total synthesis of all stereoisomers of tarchonanthuslactone from (R)- or (S)-3-hydroxybutyrate via eight steps. The key steps of the synthesis include a highly diastereoselective chelation-controlled Mukaiyama aldol reaction of a p-methoxybenzyl-protected aldehyde and a Yamaguchi lactonization of a δ-hydroxy-trans-α,β-unsaturated carboxylic acid.
Keywords: total synthesis; tarchonanthuslactone; chelation-controlled Mukaiyama aldol reaction; δ-hydroxy-trans-α,β-unsaturated carboxylic acid; Yamaguchi lactonization